Crystallographic Evidence for Direct Metal–Metal Bonding in a Stable Open‐Shell La2@Ih‐C80 Derivative. Issue 13 (25th February 2016) - Bao, Lipiao; Chen, Muqing; Pan, Changwang; Yamaguchi, Takahisa; Kato, Tatsuhisa; Olmstead, Marilyn M.; Balch, Alan L.; Akasaka, Takeshi; Lu, Xing
Abstract: Endohedral metallofullerenes (EMFs) have novel structures and properties that are closely associated with the internal metallic species. Benzyl radical additions have been previously shown to form closed‐shell adducts by attaching an odd number of addends to open‐shell EMFs (such as Sc3 C2 @ Ih ‐C80 ) whereas an even number of groups are added to closed‐shell EMFs (for example Sc3 N@ Ih ‐C80 ). Herein we report that benzyl radical addition to the closed‐shell La2 @ Ih ‐C80 forms a stable, open‐shell monoadduct instead of the anticipated closed‐shell bisadduct. Single‐crystal X‐ray diffraction results show the formation of a stable radical species. In this species, the La−La distance is comparable to the theoretical value of a La−La covalent bond and is shorter than reported values for other La2 @ Ih ‐C80 derivatives, providing unambiguous evidence for the formation of direct La−La bond. Abstract : A stable fullerene radical La2 @ Ih ‐C80 (C7 H7 ) was synthesized and fully characterized. The stability of the radical is attributed to the localization of the unpaired electron inside the cage, as suggested by EPR spectroscopy and DFT calculations. Metal–metal bonding is indicated by the La−La distance, which is consistent with the calculated distance, and the localization of the SOMO on the La2 unit.